Novel functionalized polymers for nanoparticle formulations with anti cancer drugs - Puri, Sanyogitta (2007)
The chemistry and structure of Poly (glycerol adipate) facilitate its substitution with various pendant functional groups leading to modifications of the physicochemical properties of the polymer. Modified backbones then can be selected based upon the properties of the compound to be incorporated. Thus, this could be explored as a drug delivery system without many of the limitations of commercially available polymers. The aim of this study was investigate whether various polymers and drugs interact in a specific manner and whether the nature of these interactions influence the physicochemical characteristics of the particles and their drug loading and release profile. By investigating drugs belonging to various classes and with different properties it has been possible to correlate properties associated with drugs and pendant functional groups of the polymer which are ultimately responsible for the drug loading and release characteristics. For some drug polymer formulations, good loading and controlled release rates have been achieved. Compared to various conventional polymer systems reported for nanoparticle formulations, poly (glycerol adipate) polymers have also demonstrated the ability to control rate of release of highly water soluble drugs, even from the most hydrophilic polymer backbone in its unsubstituted form. From the various drug loading and release profiles it has been demonstrated that, unlike reported literature, particle size is not the primary factor influencing drug release over the relatively small range of particle sizes seen in this study. Neither is the water solubility of either the drug or the polymer alone responsible for the rapid and uncontrolled release profile from nanoparticles.